Assessment on antioxidant activity and physical characteristics of spray dried mahkota dewa fruit extracts - M. N., Kathiman; Siti Kholijah, Abdul Mudalip; Jolius, Gimbun; Rohaida, Che Man; Zatul Iffah, Mohd Arshad; Siti Zubaidah, Sulaiman; Shalyda, Md Shaarani (IOP Publishing, 2020)
This paper presents the encapsulation of Phaleria Macrocarpa Scheff. Boerl or Mahkota Dewa extracts with maltodextrin using spray drying. The extracts of dried Mahkota Dewa fruit was obtained using subcritical water extraction process. The inlet dry air temperatures of the spray drying process was investigated at 100 °C, 125 °C, 150 °C, 175 °C and 200 °C. The spray dried powder was characterised for antioxidant activity, moisture content analysis and particle size distribution analysis. Results showed that the increased of inlet air dry temperature decreased the value of antioxidant activity, moisture content and mean diameter of the particles. The inlet air dry temperature of 200°C produced 92.19±0.18% antioxidant activity, 6.82% moisture content and 8.38 μm mean diameter particle size. Thus, can be suggested as the best inlet air temperature to encapsulate Mahkota Dewa extracts with maltodextrin using spray drying technique.